Bahasa Isyarat Sebagai Cermin Karakter Anak Tunarungu di Sekolah SLB ABC Argasari Lestari - Rahmawati, Ocha Tria; Nur, Lutfi; Purwati, Purwati (Jurusan Pendidikan Luar Biasa Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2025)
This study examines the role of sign language as the main means of communication and reflection of the character of deaf children in SLB ABC Argasari Lestari. The main problem faced is children's limitations in conveying emotions and needs verbally, so the research aims to understand how sign language supports the development of children's confidence, social interaction, and character. This study uses a qualitative approach using the case study method, involving direct observation, semi-structured interviews, and documentation. The results of the study show that sign language is not only a communication tool but also reflects the unique personality of each child. Children who actively use sign language show increased confidence and the ability to interact with the environment. In addition, values such as empathy, responsibility, and courage develop through teacher guidance. Teachers play an important role in guiding the effective and ethical use of sign language. This finding confirms that sign language is a medium that supports character development and social integration of deaf children, as well as showing their uniqueness to the community